2013
DOI: 10.1002/jmr.2263
|View full text |Cite
|
Sign up to set email alerts
|

The promiscuous protein binding ability of erythrosine B studied by metachromasy (metachromasia)

Abstract: The present study aims to elucidate aspects of the protein binding ability of erythrosine B (ErB), a poly-iodinated xanthene dye and an FDA-approved food colorant (FD&C Red No. 3), which we have identified recently as a promiscuous inhibitor of protein–protein interactions (PPI) with a remarkably consistent median inhibitory concentration (IC50) in the 5–30 µM range. Because ErB exhibits metachromasy, i.e., color change upon binding to several proteins, we exploited this property to quantify its binding to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…These compounds not only successfully inhibited the binding of recombinant hOX40L protein to the plate bound hOX40 with IC 50 s in the low micromolar range (~2 μM), but also showed acceptable target specificities when compared to several other ligand–receptor pairs within the TNFSF (RANK-RANKL, 4-1BB-4-1BBL, CD40-CD40L, and TNFR1-TNF-α) in similar experimental settings as the OX40-OX40L binding assay. Subsequent studies in an OX40 expressing NF-κB reporter HEK cell line, similar to those used previously [29, 203], indicated that 13 acts as a partial agonist [204, 205]. It produces only a lower maximum activation than the natural ligand OX40L, and in the presence of sufficiently high OX40L, it actually slightly decreases activation.…”
Section: Ox40–ox40lmentioning
confidence: 65%
See 1 more Smart Citation
“…These compounds not only successfully inhibited the binding of recombinant hOX40L protein to the plate bound hOX40 with IC 50 s in the low micromolar range (~2 μM), but also showed acceptable target specificities when compared to several other ligand–receptor pairs within the TNFSF (RANK-RANKL, 4-1BB-4-1BBL, CD40-CD40L, and TNFR1-TNF-α) in similar experimental settings as the OX40-OX40L binding assay. Subsequent studies in an OX40 expressing NF-κB reporter HEK cell line, similar to those used previously [29, 203], indicated that 13 acts as a partial agonist [204, 205]. It produces only a lower maximum activation than the natural ligand OX40L, and in the presence of sufficiently high OX40L, it actually slightly decreases activation.…”
Section: Ox40–ox40lmentioning
confidence: 65%
“…Planar or partially planar aromatic and hydrophobic residues are indeed over-represented at PPI interfaces [26, 27]. Recently, even promiscuous small-molecule PPI inhibitors have been identified [28, 29]. The ability to target PPIs could considerably enlarge the number of feasible therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…This sensor cell line was generated by stable transfection of HEK293 cells with the human CD40 gene and an NF-κB-inducible SEAP construct, which consists of the SEAP reporter gene under the control of the IFN-β minimal promoter fused to five NF-κB (and five AP-1) binding sites. As before [23], cells were cultured and assayed for activation as recommended by the manufacturer. Briefly, the cells were cultivated in Dulbecco’s Modified Eagle (DMEM) media supplemented with 4.5 g/L glucose, 10% v/v FBS, 50 U/mL penicillin, 50 μg/mL streptomycin, 100 μg/mL Normocin, and 2 mM l -glutamine.…”
Section: Methodsmentioning
confidence: 99%
“…We are using these readily available cells as a standard cell-based model to assess ligand-induced receptor activation for selected members of the tumor necrosis superfamily (TNFSF) in our work focusing on small-molecule costimulatory modulation [22, 23]. Here, we evaluated the suitability of this model to quantitate glucocorticoid activity both in a detailed full dose-response format as well as in a single-dose format.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies suggested various scaffolds, many of them based on flat aromatic structures, as appropriate for design of effective SMPPIIs [108110]. Notably, along these lines, we have identified certain xanthene-based organic dyes, such as erythrosine B and rose bengal, as the first promiscuous SMPPIIs [111, 112]. While their inhibitory mechanism is not entirely clear, it might be related to their rigid flat structures, since planar or partially planar aromatic and hydrophobic residues are over-represented at PPI interfaces [113], and they may make the binding of such structures here particularly likely.…”
Section: Small-molecule Ppi Inhibitorsmentioning
confidence: 96%